The Wanderer: Acute Abdomen Secondary to a Wandering Spleen - Toni Lombardo; Rishi R. Shah; Joseph Mazzie (Case Reports in Radiology)
Wandering spleen is a rare condition resulting from the absence or laxity of peritoneal attachments, allowing the spleen to migrate within the abdominal cavity. While some patients may remain asymptomatic, others can develop life-threatening complications such as splenic torsion, infarction, and bowel obstruction. This case report highlights one of the complications of wandering spleen and the importance of timely diagnosis and intervention.